2004
DOI: 10.1042/bst0320298
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomics, gene discovery and the ideal biocatalyst

Abstract: With the rapid development of powerful protein evolution and enzyme-screening technologies, there is a growing belief that optimum conditions for biotransformation processes can be established without the constraints of the properties of the biocatalyst. These technologies can then be applied to find the "ideal biocatalyst" for the process. In identifying the ideal biocatalyst, the processes of gene discovery and enzyme evolution play major roles. However, in order to expand the pool genes for in vitro evoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 17 publications
0
11
0
1
Order By: Relevance
“…Metagenomics has led to the discovery and characterisation of a wide range of biocatalysts, revealing much about the natural diversity of enzymes and factors which influence their functions, and making detection and optimisation of biocatalysts for specific processes a real possibility [28]. One of the main approaches to novel biocatalyst detection involves functional screening which requires gene expression in a heterologous background, usually Escherichia coli [29].…”
Section: Biotechnological Advancesmentioning
confidence: 99%
“…Metagenomics has led to the discovery and characterisation of a wide range of biocatalysts, revealing much about the natural diversity of enzymes and factors which influence their functions, and making detection and optimisation of biocatalysts for specific processes a real possibility [28]. One of the main approaches to novel biocatalyst detection involves functional screening which requires gene expression in a heterologous background, usually Escherichia coli [29].…”
Section: Biotechnological Advancesmentioning
confidence: 99%
“…[133,134], are popular targets for bioprospecting on the basis that their gene products are very likely to be adapted to function optimally under the specific extreme conditions [135][136][137]. A number of AcXEs have been identified from thermophiles and hyperthermophiles, including Caldicellulosiruptor owensensis [103], Thermomonospora fusca [138], Thermoanaerobacterium sp.…”
Section: Acxes From Extremophilesmentioning
confidence: 99%
“…The microbiome can potentially provide a wide range of novel enzymes and biocatalysts with major applications in the marketplace, for example the biotechnology, biofuels and pharmaceutical industry (Cowan et al, 2004). Hess et al (2011), through an extended metagenomic study, reported over 2.5 million novel genes and identified more than 27,000 putative carbohydrate-active enzymes with cellulolytic function.…”
Section: Introductionmentioning
confidence: 99%